Les points de contrôle routier en Guyane française : des postes-frontières comme les autres ? - Thierry Nicolas (Confins)
French Guiana is characterized by a national road network stretching just under 500 km parallel to the coast. However, this apparent modesty contrasts with its structuring role in the organization of the territory. The two axes that comprise it (RN 1 and RN2) connect the border rivers to the Cayenne conurbation and to Kourou which concentrate the bulk of the Guyanese economic activity. Main vector of trade from East to West, with the end of maritime cabotage and the weakness of air traffic, the national road network has also become the medium through which people and goods transit illegally. Faced with this situation, the authorities have set up road control posts to regulate this shady mobility. Nearly a hundred kilometers from the Maroni River and about 80 km from the Oyapock River, these «checkpoints» managed by the National Gendarmerie testify to the establishment of zones of inward flexibilization of the borders.